2017
DOI: 10.1080/23744235.2017.1312667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital malaria in newborns of mothers co-infected with HIV and malaria in Benin city

Abstract: Babies born to mothers co-infected with HIV and malaria are at increased risk for CM. All babies born by HIV positive mothers should be screened for CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[119] Newborns of mothers co-infected with HIV and malaria are at high risk of congenital malaria when maternal CD4 count is <200 cells/μl. [120] Among children with cerebral malaria, HIV-coinfection is associated with marked blunting of the inflammatory response but does not affect parasite density or outcome. [121] Tuberculosis (TB) is a leading cause of death among HIV+ individuals worldwide.…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…[119] Newborns of mothers co-infected with HIV and malaria are at high risk of congenital malaria when maternal CD4 count is <200 cells/μl. [120] Among children with cerebral malaria, HIV-coinfection is associated with marked blunting of the inflammatory response but does not affect parasite density or outcome. [121] Tuberculosis (TB) is a leading cause of death among HIV+ individuals worldwide.…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Rarely, maternal history of malaria may not be reported and, therefore, it cannot be considered as a criterion for the diagnosis of congenital malaria [17]. Origin from endemic countries for malaria, fever during pregnancy, placental malaria and anaemia in the mother, are the main risk factors [1, 8].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of congenital malaria is highly variable. The literature reported an incidence between 7 and 33% in endemic area [6, 7] with an apparent increasing rate during the last years as result of rising drug resistance, increasing virulence of the parasite, human immunodeficiency virus (HIV) infection [7, 8]. The high variability seems related to several factors such as the different diagnostic methods and sampling (cord blood vs peripheral blood) used to detect Plasmodium spp., and the area in which the epidemiologic analyses are performed [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from previous studies demonstrated that serum iron reduction among HIV-malaria co-infected patients compared to HIV-seropositive malaria negative individuals, similar to what was observed among asymptomatic HIV-malaria co-infected patients, and unlike among symptomatic HIV-malaria co-infected individuals (Onyenekwe et al, 2008). A relatively lower albumin concentration was reported by Gossele et al 2007 among HIV positive patients (Gossele, Onwuliri, & Onwuliri, 2007), while congenital malaria was observed among new-borns of co-infected mothers (Eki-Udoko, Sadoh, Ibadin, & Omoigberale, 2017). Notable impacts of malaria on biochemical indicators were observed among HIV positive patients with a rapid reduction of serum iron (Onyenekwe et al, 2007).…”
Section: Effect Of Hiv-malaria Co-infection In Nigeriamentioning
confidence: 97%